2023
DOI: 10.3390/nano13091440
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials as Promising Additives for High-Performance 3D-Printed Concrete: A Critical Review

Abstract: Three-dimensional (3D) printed concrete (3DPC), as one of the subset of digital fabrication, has provided a revolution in the construction industry. Accordingly, scientists, experts, and researchers in both academic and industry communities are trying to improve the performance of 3DPC. The mix design of all kinds of concrete has always been the most crucial property to reach the best efficiency. Recently, many studies have been performed to incorporate nano- and micro-scale additives to ameliorate the propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 237 publications
0
2
0
Order By: Relevance
“…This SDG could also be improved by conducting essential research on the management and/or disposal of exhausted ZnO/MgO photocatalysts. For Instance, Razzaghian Ghadikolaee et al [56] found that the photocatalyst material after exhaustion could be managed by using it as an attractive additive to maintain better 3D-printed concrete properties.…”
Section: Meeting the Sustainability Dimensions From The Photocatalyti...mentioning
confidence: 99%
See 1 more Smart Citation
“…This SDG could also be improved by conducting essential research on the management and/or disposal of exhausted ZnO/MgO photocatalysts. For Instance, Razzaghian Ghadikolaee et al [56] found that the photocatalyst material after exhaustion could be managed by using it as an attractive additive to maintain better 3D-printed concrete properties.…”
Section: Meeting the Sustainability Dimensions From The Photocatalyti...mentioning
confidence: 99%
“…Applying these eco-friendly and cleaner techniques to synthesize the ZnO/MgO could reduce the chemical costs and minimize exposure to possible material toxicity. Where the recyclability of the spent catalyst material is concerned, the ZnO/MgO nanocomposite should be tested for applications as an additive in the construction industry, following previous research [56]. This benefit would avoid the unrestricted disposal of solid waste to the terrestrial and inland freshwater ecosystems and the related services, meeting the targets of SDG15 "Life on Land".…”
Section: Meeting the Sustainability Dimensions From The Photocatalyti...mentioning
confidence: 99%